MAKNA DAN NILAI PENDIDIKAN ISLAM DALAM TRADISI REJEBAN: STUDI KASUS DI DUSUN GOWOK RINGIN, MAGELANG - Cahya Manggali (Taskuliah Edukasi Indonesia, 2025)
This study aims to explore the Islamic educational values embedded in the Rejeban tradition, a local cultural practice held annually in Gowok Ringin Hamlet, Sengi Village, Dukun District, Magelang Regency. The research was motivated by the significance of preserving cultural traditions that convey educational and religious messages, especially within rural Islamic communities. While numerous studies have examined Islamic education and local culture, the exploration of Islamic educational values embedded in village-based cultural rituals like Rejeban remains limited and underexplored. This research employs a qualitative case study method with a socio-anthropological approach. Data were collected through observation, documentation and interviews with five key informants, including traditional leaders, the hamlet head, committee heads, religious scholars, and local community members. The Rejeban tradition consists of a series of events including cemetery pilgrimage, communal feasting (ngetokke), and an overnight wayang kulit (shadow puppet) performance. These rituals embody various Islamic educational values: religious (spiritual reflection, gratitude, and remembrance of death), cultural (preservation of Javanese-Islamic heritage), and social (solidarity, cooperation, and hospitality). The tradition serves as a medium for intergenerational transmission of local Islamic wisdom. While the study successfully identifies educational values in the Rejeban tradition, it is limited to one geographical context. The implications of this study suggest the potential of integrating local culture into Islamic education. However, further research across diverse communities is needed to generalize the findings and deepen the theoretical framing. This paper contributes to the discourse on the intersection of Islamic education and local tradition, offering a case study of how cultural practices can embody and transmit religious values. It highlights the importance of context-based Islamic pedagogy that honors local wisdom while fostering religious understanding.